FORMULASI SEDIAAN SABUN CAIR ANTIBAKTERI MINYAK ATSIRI DAUN KEMANGI (Ocimumamericanum L.) DAN UJI TERHADAP BAKTERI Staphylococcus epidermidis dan Staphylococcus aureus - Febry Astuti Abu; Yusriadi Yusriadi; Muhammad Rinaldhi Tandah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Basil (Ocimum americanum L.) is a plant that has antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis that is a bacteria can cause infection. Basil contains essential oils that act as an antibacterial. This research aims to formulate the essential oil of basil leaves into a liquid soap, determine antibacterial activity against S.aureus and S.epidermidis bacteria with the agar diffusion method using wells and determine the stability of the preparation. Antibacterial activity data that gain was analyzed by one-way ANOVA with a level of trust 95% followed by Duncan test. The results of the research showed basil essential oil liquid soap preparation has antibacterial activity. The analysis results showed that there were significant differences in the concentration of 2%, 3%, 4%, and the Duncan test results showed no significant difference between the concentration of 4% with control (+). The results of the t-student analysis of liquid soap include viscosity, pH and dispersive capacity does not fill the parameters of stability during the storage period of 28 days